Encountering publicness and multiculture: public pedagogy with a multilingual community choir - Dieckmann, SS (Society for Ethnomusicology, 2025)
This article presents an ethnography of Lullaby Train: public art performances by a multilingual community choir in Melbourne, Australia. Singing lullabies on trains and platforms produced encounters that were notably distinct from those experienced within the Lullaby Choir itself, as well as in performances attended by self-selecting audiences. Lullaby Train was designed to revitalize particular modes of civic engagement, but instead produced conflicting forms of publicness and multiculture. Examining these performances as pedagogical sites, I argue that the quotidian interactions that characterize urban social relations provide important insights for the study and practice of intercultural music.